Analysis of data types in "Comenius Logo" - Dagienė, Valentina (Lietuvos matematikos rinkinys, 1999)
This paper deals with two standpoint of data types in "Comenius Logo". The traditional one considers three kinds of "Comenius Logo" data structures: words, images, and lists. The modern standpoint pick out three mechanisms of forming and exploring data: primitive data (to represent basic entities of the programming languages); means of combination (to build compound data from simple ones); means of abstraction (to name compound objects and manipulate them as units). Some examples of developing new data are presented.